La naturaleza y el mundo romano: Las Églogas y Virgilio (Iter, 2022)
In the present work we will try to elucidate the union between the naturerepresented in this case by pastors who perform their ordinary tasks relatingto problems that were crucial in the Roman world, such as the expropriation of property, love for a slave, economic power , arbitration as a way to solve conflicts, thedivinization of Emperor Augustus.For this we will devote ourselves to the study of one of the most beautifulcompositions of antiquity, the Bucólicas de Virgilio. It is precisely in the pen of thisgenius of Latin letters that we can find vulgar man in his natural environment bydeciding on these crucial issues the Roman citizen.Before introducing ourselves to the analysis of the eclogues in question wewill know a little about the poet and his environment, how much of his personalproblems and experiences influenced his verses, without asking too much since wewould escape from the proposed objective.
Keywords: nature - roman world - eclogues - Virgil